EFEK PENYIMPANAN TERHADAP VIRULENSI NUCLEAR POLYHEDROSIS VIRUS YANG DIAPLIKASIKAN PADA TANAMAN KEDELAI TERSERANG ULAT GRAYAK (Spodoptera litura Fabr. ) - Sudi Pramono . (Universitas Lampung, 2001)
One of the problem increased soybean production was Spodoptera litura (army worm), because army worm has been known to be resistant to many insec¬ticides. Alternatif control techniques should be explored to reduce population of the pest. Nuclear Polyhedrosis Virus (NPV) could storage one or more year, but must used technique cold storage so that not virulence decreased. This experiment was conducted to study (1) NPV patho¬genicity to army worm in the field, and (2) the effect of storage on the pathogenicity of NPV to S. litura. The research consisted of two experiments i.e. laboratory and field experiments. Each experiment had seven treatments arranged in a randomized completely block design. Each treatment was replicated four times. The results show the highest mortality of S. litura occurred in plot treated with 1,0 x 107 PIBs /ml, the mortality was 48 to 49,33 spec/plot after ten days aplicated . If comparative patogenicity the new and the old NPV was not significant. Population of army worm decreased significantly by NPV and control. So that patogenecity NPV storage one year as well as new NPV against army worm.